A hollow indium zinc sulfide composite catalytic material loaded with a dual promoter and a preparation method and application thereof
By designing a composite material of MnO2@ZnIn2S4@Ti3C2, the problem of low photocatalytic efficiency of ZnIn2S4 material was solved, and high efficiency of photocatalytic water splitting for hydrogen production and benzaldehyde synthesis was achieved, with a significant improvement in hydrogen production rate and synthesis rate.
Patent Information
- Application Number
- CN202511471070.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-12-23
- Estimated Expiration
- 2045-10-15
AI Technical Summary
ZnIn2S4 materials suffer from low efficiency in photocatalytic water splitting for hydrogen production and synthesis of high-value-added chemicals due to the rapid recombination rate and poor transfer ability of photogenerated electrons and holes.
A composite material of MnO2@ZnIn2S4@Ti3C2 is used, in which MnO2 is a hollow sphere structure, ZnIn2S4 is a two-dimensional sheet structure, and Ti3C2 is attached to the surface of the composite sphere structure to form a hollow composite catalyst. MnO2 and Ti3C2 act as hole-type and electron-type co-catalysts, respectively, to enhance the separation ability of photogenerated electrons and holes and increase the specific surface area.
It significantly improved the efficiency of photocatalytic water splitting for hydrogen production and benzaldehyde synthesis, increasing the hydrogen production rate from 1.60 mmol g⁻¹h⁻¹ to 4.30 mmol g⁻¹h⁻¹ and the benzaldehyde synthesis rate to 2.1 mmol g⁻¹h⁻¹, thereby enhancing photocatalytic activity and reactive sites.
Smart Images

Figure CN120939970B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of photocatalytic water splitting to produce hydrogen, and relates to a hollow indium zinc sulfide (ZnIn2S4) composite catalytic material loaded with double cocatalysts and a preparation method and application thereof. BACKGROUND
[0002] The information disclosed in this Background section is for the purpose of increasing the understanding of the background of the application without admitting that any of the information constitutes prior art.
[0003] ZnIn2S4 is a two-dimensional sheet structure, and has adjustable energy band structure, low toxicity and good chemical stability. However, the practical application of ZnIn2S4 is limited by its low surface activity and slow photogenerated carrier transfer rate, which leads to problems such as fast recombination rate of photogenerated electrons and holes and poor transfer ability, thereby affecting the efficiency of photocatalytic water splitting to produce hydrogen and synthesis of high-value-added chemicals. SUMMARY
[0004] In order to solve the problems in the prior art, the application aims to provide a hollow indium zinc sulfide composite catalytic material loaded with double cocatalysts and a preparation method and application thereof. The MnO2@ZnIn2S4@Ti3C2 composite material provided by the application can effectively separate photogenerated electrons and holes, increase active sites of photocatalytic reaction, accelerate the transport and separation of carriers, and thus significantly improve the efficiency of photocatalytic water splitting to produce hydrogen coupled with synthesis of benzaldehyde.
[0005] In order to achieve the above-mentioned purposes, the technical scheme of the application is as follows:
[0006] In a first aspect, the application provides a hollow indium zinc sulfide composite catalytic material loaded with double cocatalysts, which is a material composed of double metal chalcogenide ZnIn2S4 and MnO2 and Ti3C2. The MnO2 has a hollow spherical structure, the ZnIn2S4 has a two-dimensional sheet structure, the ZnIn2S4 is coated on the outer surface of the MnO2 to form a composite spherical structure, and the Ti3C2 is attached to the surface of the composite spherical structure.
[0007] The composite catalytic material provided by the application is a MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure. The MnO2 and the Ti3C2 are loaded on the two side surfaces of the ZnIn2S4, respectively. The MnO2 and the Ti3C2 cocatalysts play the roles of hole-type and electron-type cocatalysts, respectively. The MnO2 can enrich photogenerated holes, and the Ti3C2 can collect photogenerated electrons. The above-mentioned characteristics not only enhance the separation ability of photogenerated electrons and holes, but also increase the redox reaction active sites by increasing the specific surface area, and greatly expand the visible light absorption range of the material. The synergistic effect of the above-mentioned characteristics makes the composite material exhibit excellent photocatalytic activity.
[0008] In addition, the present application accidentally discovers, through experiments, that, compared with pure ZnIn2S4 catalytic materials, adding the cocatalysts MnO2 and Ti3C2 can significantly improve the photocatalytic activity of the MnO2@ZnIn2S4@Ti3C2 composite catalytic material, for example, the hydrogen production rate can be increased from 1.60 mmol g-1 h-1 (pure two-dimensional sheet ZnIn2S4) to 4.30 mmol g-1 h-1 (cocatalyst-loaded hollow MnO2@ZnIn2S4@Ti3C2). -1 h -1 (pure two-dimensional sheet ZnIn2S4) to 4.30 mmol g-1 h-1 (cocatalyst-loaded hollow MnO2@ZnIn2S4@Ti3C2). -1 h -1 (cocatalyst-loaded hollow MnO2@ZnIn2S4@Ti3C2).
[0009] In another aspect, a preparation method of a hollow indium zinc sulfide composite catalytic material loaded with double cocatalysts comprises the following steps:
[0010] providing MnO2 with a hollow sphere structure;
[0011] mixing the MnO2 with a hollow sphere structure with zinc salt, indium salt and sulfur source, and then performing synthesis of indium zinc sulfide, so that the indium zinc sulfide is coated on the surface of the MnO2 with a hollow sphere structure, to obtain a composite sphere structure;
[0012] mixing the composite sphere structure with Ti3C2 under an inert atmosphere, so that the Ti3C2 is attached to the surface of the composite sphere structure.
[0013] The present application finds, through experiments, that the MnO2@ZnIn2S4@Ti3C2 composite material obtained by the above treatment on the hollow MnO2 sphere not only retains the hollow structure, but also loads the redox double cocatalysts.
[0014] In a third aspect, the hollow indium zinc sulfide composite catalytic material is applied to photocatalytic decomposition of water to produce hydrogen and coupling synthesis of benzaldehyde.
[0015] The present application has the following beneficial effects:
[0016] The hollow indium zinc sulfide composite catalytic material loaded with double cocatalysts provided by the present application sets the MnO2 and Ti3C2 on the two side surfaces of ZnIn2S4, which not only retains the effect of the redox cocatalyst, but also has a hollow structure, provides more opportunities for reflection and refraction of light, improves the light absorption and utilization efficiency, increases the active sites and specific surface area of the reaction, and is beneficial to adsorption of the reactants. The MnO2 and Ti3C2 cocatalysts have the effects of hole-type and electron-type cocatalysts, respectively, so as to enrich holes and electrons, respectively, promote directional migration of the photo-generated carriers, realize migration of the photo-generated electrons and holes to different active sites, respectively, form a redox reaction partition, and thus exhibit excellent photocatalytic activity.
[0017] The present application utilizes MnO2 with a hollow sphere structure to react with zinc salt, indium salt and sulfur source to generate MnO2@ZnIn2S4 composite material, and then under the condition of inert atmosphere, Ti3C2 is loaded on the outer surface of the MnO2@ZnIn2S4 composite material, so as to obtain the hollow indium zinc sulfide composite catalytic material loaded with the double-assisted catalyst of the present application. The preparation method of the present application has simple steps and low energy consumption, and is conducive to industrialized production. BRIEF DESCRIPTION OF DRAWINGS
[0018] The drawings accompanying the specification of the present application serve to provide further understanding of the present application, and the illustrative embodiments of the present application and the description thereof serve to explain the present application, and do not constitute an improper limitation on the present application.
[0019] Figure 1 is the X-ray diffraction pattern (XRD) of the hollow MnO2 material, the flaky ZnIn2S4 material, the flaky Ti3C2 material, the MnO2@ZnIn2S4 composite material with a hollow structure and the MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure prepared in Examples 2, 3, 4, 6, 9 of the present application.
[0020] Figure 2 is the scanning electron microscope (SEM) of the carbon sphere material prepared in Example 1 of the present application.
[0021] Figure 3 is the transmission electron microscope (TEM) of the MnO2 material with a hollow structure prepared in Example 2 of the present application.
[0022] Figure 4 is the transmission electron microscope (TEM) of the MnO2@ZnIn2S4 composite material with a hollow structure prepared in Example 6 of the present application.
[0023] Figure 5 is the transmission electron microscope (TEM) of the MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure prepared in Example 9 of the present application.
[0024] Figure 6 is the photocatalytic water decomposition hydrogen production performance diagram of the MnO2 material with a hollow structure, the flaky ZnIn2S4 material, the flaky Ti3C2 material, the MnO2@ZnIn2S4 composite material with a hollow structure and the MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure prepared in Examples 2, 3, 4, 5, 6, 7, 8, 9, 10 of the present application.
[0025] Figure 7The figure is a performance diagram of photocatalytic synthesis of benzaldehyde of the MnO2 material with a hollow structure, the flaky ZnIn2S4 material, the flaky Ti3C2 material, the MnO2@ZnIn2S4 composite material with a hollow structure and the MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure prepared by the embodiments 2, 3, 4, 5, 6, 7 and 8 of the application. DETAILED DESCRIPTION
[0026] It should be noted that the following detailed description is exemplary in nature and is intended to provide further description of the application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
[0027] It is to be understood that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of example embodiments in accordance with the present application. As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise. It will be further understood that the terms "comprises" and / or "comprising," when used in this specification, specify the presence of stated features, steps, operations, elements, components, and / or groups thereof, but do not preclude the presence or addition of one or more other features, steps, operations, elements, components, and / or groups thereof.
[0028] In view of the fact that the efficiency of photocatalytic decomposition of water to produce hydrogen coupled with synthesis of benzaldehyde and other high value-added chemicals by ZnIn2S4 is still to be improved, and the application of ZnIn2S4 loaded with a cocatalyst is relatively less, in order to further solve the problem of low photocatalytic efficiency of ZnIn2S4 material, the application provides a hollow indium zinc sulfide composite catalytic material loaded with double cocatalysts and a preparation method and application thereof.
[0029] In a typical embodiment of the application, a hollow indium zinc sulfide composite catalytic material loaded with double cocatalysts is provided, which is a material in which a double metal chalcogenide ZnIn2S4 is compounded with MnO2 and Ti3C2, the MnO2 has a hollow spherical structure, the ZnIn2S4 has a two-dimensional flaky structure, the ZnIn2S4 is coated on the outer surface of the MnO2 to form a composite spherical structure, and the Ti3C2 is attached to the surface of the composite spherical structure.
[0030] In some embodiments, in the composite spherical structure, the mass ratio of the MnO2 to the ZnIn2S4 is 1:13.2-32.33.
[0031] In some embodiments, in the composite spherical structure, the mass ratio of the Ti3C2 to the composite spherical structure is 0.021-0.041:1. When the mass ratio of the Ti3C2 to the composite spherical structure is 0.029-0.031:1, the components in the composite catalytic material have a better synergistic effect, and the catalytic performance of the composite catalytic material in photocatalytic decomposition of water to produce hydrogen coupled with synthesis of benzaldehyde can be more significantly improved.
[0032] In another embodiment of the present application, a method for preparing a hollow indium zinc sulfide composite catalyst material loaded with a dual promoter is provided, comprising the following steps:
[0033] MnO2 with a hollow sphere structure is provided;
[0034] MnO2 with a hollow sphere structure is mixed with a zinc salt, an indium salt and a sulfur source, and then indium zinc sulfide is synthesized, so that the indium zinc sulfide is coated on the surface of the MnO2 with a hollow sphere structure, and a composite sphere structure is obtained;
[0035] The composite sphere structure is mixed with Ti3C2 under an inert atmosphere, so that the Ti3C2 is attached to the surface of the composite sphere structure.
[0036] The MnO2 with a hollow sphere structure can be prepared by a known method. At present, a commonly used method for preparing the MnO2 with a hollow sphere structure is a template method. In some embodiments, the preparation process of the MnO2 with a hollow sphere structure is as follows: carbon spheres are uniformly mixed with a potassium permanganate aqueous solution, a C@MnO2 composite material is prepared by a hydrothermal method, and then C is removed by calcination. Specifically, the mass ratio of the carbon spheres to the potassium permanganate is 1:1.2-1.5. The hydrothermal method refers to a treatment method in which water is used as a solvent, and the reaction system is heated under a closed condition to increase the pressure and then react. Specifically, in the preparation process by the hydrothermal method, the temperature is 115-125 ℃, and the time is 2-4 h. Specifically, the calcination treatment time is 2-3 h. Specifically, the heating mode of the calcination treatment is programmed heating. The programmed heating refers to a heating mode in which heating is performed at a certain heating rate. More specifically, the heating rate of the programmed heating is 4.8-5.2 ℃ / min -1 .
[0037] The carbon spheres used in the present application can be obtained by a known method, for example, by hydrothermal preparation of glucose or sucrose. Specifically, the sucrose is treated by hydrothermal treatment. The hydrothermal treatment refers to a treatment by the hydrothermal method. Specifically, the temperature of the hydrothermal treatment is 160-180 ℃, and the time is 2-4 h.
[0038] In some embodiments, the mass ratio of the MnO2 with a hollow sphere structure to the zinc salt, the indium salt and the sulfur source is 1:5-7:24-28:12-18, and preferably 1:6-6.8:25-26.2:11-13.4.
[0039] The zinc salt used in the present application refers to a compound in which the cation is a zinc ion, for example, zinc chloride, zinc sulfate, zinc nitrate, zinc acetate, etc.
[0040] The indium salt used in the present application refers to a compound in which the cation is an indium ion, for example, indium sulfate, indium nitrate, indium chloride, etc.
[0041] The sulfur source described in the present application refers to a compound capable of providing sulfur element for zinc-indium sulfide, such as thioacetamide, sulfide (sodium sulfide, potassium sulfide), sulfur, etc.
[0042] In some embodiments, the temperature for synthesizing the zinc-indium sulfide is 70-90 ℃, and the time is 2-3 h. The solvent system for synthesizing the zinc-indium sulfide is a mixed solution of glycerol and water, specifically, the volume ratio of glycerol to water is 1:8.5-9.5.
[0043] In some embodiments, the Ti3C2 is obtained by etching Ti3AlC2 powder. Specifically, the etchant used in the etching process is hydrofluoric acid, the etching temperature is 30-40 ℃, and the etching time is 24-48 h.
[0044] In some embodiments, the temperature for mixing the composite ball structure with the Ti3C2 is 20-30 ℃, and the time is 2-4 h.
[0045] The third embodiment of the present application provides an application of the hollow zinc-indium sulfide composite catalytic material in photocatalytic decomposition of water to produce hydrogen coupled with synthesis of benzaldehyde.
[0046] Specifically, the hollow zinc-indium sulfide composite catalytic material is added to a solution containing benzyl alcohol, mixed uniformly, and irradiated.
[0047] In order to enable those skilled in the art to more clearly understand the technical solutions of the present application, the technical solutions of the present application will be described in detail below in combination with specific embodiments.
[0048] Embodiment 1:
[0049] A preparation method of a carbon ball material, comprising the following steps:
[0050] 13 g of sucrose was dissolved in 50 mL of deionized water, stirred at room temperature for 30 min to dissolve, and the clear solution was transferred to a 50 mL polytetrafluoroethylene lined reaction kettle, and hydrothermally treated in an oven at 180 ℃ for 2 h. After natural cooling to room temperature, the obtained precipitate was centrifuged, washed, dried, and ground to obtain a smooth carbon ball material.
[0051] Embodiment 2:
[0052] A preparation method of a MnO2 hollow ball material (denoted as MnO2), comprising the following steps:
[0053] 0.1 g of the smooth carbon spheres prepared in Example 1 and 0.126 g of potassium permanganate were added to 70 mL of deionized water. The mixture was sonicated for 15 min and then stirred continuously at room temperature for 30 min to form a homogeneous suspension. The resulting suspension was transferred to a 100 mL polytetrafluoroethylene-lined reactor and hydrothermally treated in an oven at 120 °C for 3 h. After natural cooling to room temperature, the resulting precipitate was centrifuged, washed, dried, and ground. The ground black powder was then placed in a tube furnace at 5 °C for 5 min. -1 The material is heated to 500 ℃ and calcined for 2 h, then naturally cooled and ground to obtain MnO2 hollow spheres.
[0054] Example 3:
[0055] A method for preparing a two-dimensional sheet-like ZnIn2S4 material (denoted as ZnIn2S4) includes the following steps:
[0056] 0.31 g of zinc chloride, 1.31 g of indium chloride tetrahydrate, and 0.67 g of thioacetamide were added to 72 mL of deionized water and 8 mL of glycerol. The mixture was stirred continuously at room temperature for 30 min. The resulting solution was transferred to a 250 mL three-necked flask and treated in an oil bath at 80 °C for 2 h. After naturally cooling to room temperature, the resulting precipitate was centrifuged, washed, dried, and ground to obtain ZnIn2S4 material with a plate-like structure.
[0057] Example 4:
[0058] A method for preparing a Ti3C2 material (denoted as Ti3C2) with a layered structure includes the following steps:
[0059] 1 g of Ti3AlC2 powder was slowly added to 20 mL of hydrofluoric acid solution and stirred continuously at 35 °C for 48 h to form a suspension. The resulting suspension was centrifuged, washed with deionized water until pH > 6, and freeze-dried to obtain a black powder. The black powder was dispersed in 20 mL of dimethyl sulfoxide solution and stirred under nitrogen protection for 24 h. After centrifugation and washing with dimethyl sulfoxide, the black suspension was freeze-dried to prepare a concentration of 1 g L⁻¹. -1 Ti3C2 solution.
[0060] Example 5:
[0061] A method for preparing a hollow MnO2@ZnIn2S4 composite material (denoted as MZ-93) includes the following steps:
[0062] MnO2 hollow spheres prepared in Example 2 were added to 72 mL of deionized water and 8 mL of glycerol, and after ultrasonic treatment for 15 min, stirring was continued at room temperature for 30 min, followed by the addition of 0.16 g of zinc chloride, 0.72 g of indium chloride tetrahydrate, and 0.37 g of thioacetamide, and stirring was continued at room temperature to form a uniform suspension, and the obtained suspension was transferred to a 250 mL three-necked flask and treated in an 80 °C oil bath for 2 h. After natural cooling to room temperature, the obtained precipitate was centrifuged, washed, dried, and ground to obtain a MnO2@ZnIn2S4 composite material with a hollow structure.
[0063] Example 6:
[0064] A method for preparing a MnO2@ZnIn2S4 composite material with a hollow structure (denoted as MZ-95) includes the following steps:
[0065] MnO2 hollow spheres prepared in Example 2 were added to 72 mL of deionized water and 8 mL of glycerol, and after ultrasonic treatment for 15 min, stirring was continued at room temperature for 30 min, followed by the addition of 0.24 g of zinc chloride, 1.03 g of indium chloride tetrahydrate, and 0.53 g of thioacetamide, and stirring was continued at room temperature to form a uniform suspension, and the obtained suspension was transferred to a 250 mL three-necked flask and treated in an 80 °C oil bath for 2 h. After natural cooling to room temperature, the obtained precipitate was centrifuged, washed, dried, and ground to obtain a MnO2@ZnIn2S4 composite material with a hollow structure.
[0066] Example 7:
[0067] A method for preparing a MnO2@ZnIn2S4 composite material with a hollow structure (denoted as MZ-97) includes the following steps:
[0068] MnO2 hollow spheres prepared in Example 2 were added to 72 mL of deionized water and 8 mL of glycerol, and after ultrasonic treatment for 15 min, stirring was continued at room temperature for 30 min, followed by the addition of 0.41 g of zinc chloride, 1.76 g of indium chloride tetrahydrate, and 0.91 g of thioacetamide, and stirring was continued at room temperature to form a uniform suspension, and the obtained suspension was transferred to a 250 mL three-necked flask and treated in an 80 °C oil bath for 2 h. After natural cooling to room temperature, the obtained precipitate was centrifuged, washed, dried, and ground to obtain a MnO2@ZnIn2S4 composite material with a hollow structure.
[0069] Example 8:
[0070] A preparation method of a hollow indium zinc sulfide composite catalytic material loaded with a double assistant catalyst (MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure, referred to as MZT-2), comprising the following steps:
[0071] 0.1 g of the MnO2@ZnIn2S4 composite material with a hollow structure prepared in Example 6 was added to 60 mL of deionized water, and after ultrasonic treatment for 15 min, it was continuously stirred at room temperature for 30 min, then 2 mL of the Ti3C2 colloidal solution prepared in Example 4 was added, and stirring was carried out under a nitrogen atmosphere for 12 h. The obtained precipitate was centrifuged, washed, vacuum dried, and ground to obtain the MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure.
[0072] Example 9:
[0073] A preparation method of a hollow indium zinc sulfide composite catalytic material loaded with a double assistant catalyst (MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure, referred to as MZT-3), comprising the following steps:
[0074] 0.1 g of the MnO2@ZnIn2S4 composite material with a hollow structure prepared in Example 6 was added to 60 mL of deionized water, and after ultrasonic treatment for 15 min, it was continuously stirred at room temperature for 30 min, then 3 mL of the Ti3C2 colloidal solution prepared in Example 4 was added, and stirring was carried out under a nitrogen atmosphere for 12 h. The obtained precipitate was centrifuged, washed, vacuum dried, and ground to obtain the MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure.
[0075] Example 10:
[0076] A preparation method of a hollow indium zinc sulfide composite catalytic material loaded with a double assistant catalyst (MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure, referred to as MZT-4), comprising the following steps:
[0077] 0.1 g of the MnO2@ZnIn2S4 composite material with a hollow structure prepared in Example 6 was added to 60 mL of deionized water, and after ultrasonic treatment for 15 min, it was continuously stirred at room temperature for 30 min, then 4 mL of the Ti3C2 colloidal solution prepared in Example 4 was added, and stirring was carried out under a nitrogen atmosphere for 12 h. The obtained precipitate was centrifuged, washed, vacuum dried, and ground to obtain the MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure.
[0078] Figure 1XRD patterns of the prepared hollow MnO2 spheres, flaky ZnIn2S4 material, Ti3C2 and MnO2@ZnIn2S4, MnO2@ZnIn2S4@Ti3C2 composite materials prepared for Examples 2, 3, 4, 6, 9, Figure 1 show the characteristic peaks of MnO2, proving that MnO2 is successfully prepared. At the same time, the characteristic peaks of ZnIn2S4 are also shown in Figure 1 , proving that ZnIn2S4 is successfully prepared. However, only the characteristic peaks of ZnIn2S4 are shown in the XRD patterns of MnO2@ZnIn2S4, MnO2@ZnIn2S4@Ti3C2 composite materials, which is mainly due to the small amount of catalyst and the XRD patterns of the prepared samples are similar to the original ZnIn2S4.
[0079] The SEM image of the carbon sphere material prepared in Example 1 is shown in Figure 2 , and the carbon material has a spherical morphology.
[0080] The TEM image of the hollow MnO2 material prepared according to Example 2 shows that the MnO2 material has a hollow structure. Figure 3
[0081] The TEM image of the hollow MnO2@ZnIn2S4 composite material prepared in Example 6 shows that the material still maintains a hollow structure. Figure 4
[0082] The hollow MnO2@ZnIn2S4@Ti3C2 composite material prepared in Example 7 still maintains a hollow spherical structure, indicating that the hollow structure of the MnO2@ZnIn2S4@Ti3C2 composite material prepared by Ti3C2 coating does not destroy the original hollow structure, as shown in Figure 5
[0083] The obtained hollow MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure is applied to photocatalytic decomposition of water to produce hydrogen and coupling synthesis of benzaldehyde, and the experimental process is as follows:
[0084] 20 mg of the photocatalyst prepared in Examples 2, 3, 4, 5, 6, 7, 8, 9, 10 of the present application is added to 90 mL of deionized water and 100 μL of benzyl alcohol solution and ultrasonically dispersed uniformly. The suspension is moved into a reactor, a 300 W xenon lamp is used as a simulated sunlight to irradiate the reactor, an online gas chromatograph equipped with a thermal conductivity detector is used to detect the amount of hydrogen generated, an online gas chromatograph equipped with a flame ionization detector is used to detect the amount of benzaldehyde generated, and the efficiency of the photocatalyst in producing hydrogen and synthesizing benzaldehyde is further calculated by combining the pre-prepared standard curve.
[0085] The photocatalyst prepared by the embodiments of the present application has high water decomposition hydrogen production and coupling benzaldehyde generation efficiency Figure 6 、 Figure 7 From Figure 6 、 Figure 7 it can be seen that the prepared MnO2@ZnIn2S4@Ti3C2 composite material with a hollow structure and the photocatalytic water decomposition hydrogen production and coupling benzaldehyde generation efficiency are higher than those of the two-dimensional sheet-shaped ZnIn2S4 material, especially the MZT-3 prepared in Example 9, which has a photocatalytic water decomposition hydrogen production efficiency of 4.30 mmol g -1 h -1 , about 2.7 times that of the two-dimensional sheet-shaped ZnIn2S4, and a coupling benzaldehyde generation rate of 2.1 mmol g -1 h -1 , about 1.75 times that of the two-dimensional sheet-shaped ZnIn2S4. The construction of the hollow structure and the loading of the redox cocatalyst improve the photocatalytic hydrogen production and coupling benzaldehyde generation efficiency of the composite material, which may be due to the fact that the hollow structure has a large surface area and high light collection efficiency. The presence of the cocatalyst can greatly increase the active sites and promote the efficient separation of photo-generated electrons and holes, so that the composite material exhibits excellent photocatalytic activity and realizes high redox activity. The above results show that the construction of the hollow structure and the loading of the redox cocatalyst are of great significance for improving the photocatalytic activity of the composite material.
[0086] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A hollow indium zinc sulfide composite catalytic material supported on dual co-catalysts, characterized in that it is... The material is a composite of bimetallic chalcogenide ZnIn2S4 with MnO2 and Ti3C2. MnO2 has a hollow sphere structure, ZnIn2S4 has a two-dimensional sheet structure, ZnIn2S4 coats the outer surface of MnO2 to form a composite sphere structure, and Ti3C2 is attached to the surface of the composite sphere structure. In the composite sphere structure, the mass ratio of MnO2 to ZnIn2S4 is 1:13.2~32.3; The mass ratio of Ti3C2 to the composite sphere structure is 0.029~0.031:
1.
2. A method for preparing a hollow indium zinc sulfide composite catalytic material supported on dual co-catalysts as described in claim 1, characterized in that, Includes the following steps: Provide MnO2 with a hollow spherical structure; Indium zinc sulfide is synthesized by mixing MnO2 with a hollow sphere structure with zinc salt, indium salt and sulfur source, so that indium zinc sulfide is coated on the surface of MnO2 with a hollow sphere structure to obtain a composite sphere structure. Under inert atmosphere conditions, the composite sphere structure is mixed with Ti3C2, so that Ti3C2 adheres to the surface of the composite sphere structure.
3. The preparation method according to claim 2, characterized in that, The preparation process of MnO2 with hollow sphere structure is as follows: carbon spheres are mixed evenly with an aqueous solution of potassium permanganate, and C@MnO2 composite material is prepared by hydrothermal method. Then, C is removed by calcination to obtain the final product.
4. The preparation method according to claim 2, characterized in that, The mass ratio of MnO2 with a hollow sphere structure to zinc salt, indium salt and sulfur source is 1:5~7:24~28:12~18.
5. The preparation method according to claim 2, characterized in that, The temperature for synthesizing indium zinc sulfide is 70~90 ℃, and the time is 2~3 h.
6. The preparation method according to claim 2, characterized in that, The composite sphere structure was mixed with Ti3C2 at a temperature of 20~30℃ for 2~4 h.
7. The application of the hollow indium zinc sulfide composite catalytic material according to claim 1 in the photocatalytic water splitting to hydrogen production coupled with the synthesis of benzaldehyde.
8. The application as described in claim 7, characterized in that, The hollow indium zinc sulfide composite catalyst was added to a solution containing benzyl alcohol, mixed evenly, and then irradiated with light.
Citation Information
Patent Citations
Granular manganese dioxide / titanium carbide composite material and preparation method thereof
CN108147464A
Preparation method of ultrathin Ti3C2 nanosheet / ZnIn2S4 flower ball composite photocatalyst
CN113351227A